Utilization of the Multi Attribute Utility Theory (MAUT) Method in Determining Wedding Halls in Medan City - Kadrayani Kadrayani; Hasdiana Hasdiana; Dedy Irwan; Eka Rahayu; Yulia Agustina Dalimunthe (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2023)
The building is an important part of the wedding ceremony. Especially if the event owner does not have sufficient land. So far, it's been difficult for the community to decide which wedding hall they want. Both in terms of location, building design, rental prices etc. The purpose of this research is to apply the Multi Attribute Utility Theory (MAUT) method to recommend building rental services. The criteria used to select a building are location, price, facilities, parking space capacity, and number of guests. The alternatives used are Adi Mulia Hotel Medan, Caffe Bel Mondo Medan, Andaliman Hall, Aceh Sepakat, Al-amjad Convention Hall, Wisma Mahina Center, Mutiara Suara Nafiti Convention Hall, Namaken Hall, Al-Maruf Multipurpose Building, and the Dharma Wanita Petisah Building. The results of applying the MAUT method show that the Al-Amjad Convention Hall is most recommended as the building that best fits the given criteria.